Evaluación de la contaminación acústica derivada del parque automotor en el sector centro de la ciudad de Loja - Flores Vega, Diego Armando (2014)
For the problem of vehicular noise in the city of Loja, two objectives were formulated: To characterize noise sites with higher sound pressure derivative of the fleet in the center section of the city of Loja in the period 2013 - 2014; and design control measures and mitigation of noise pollution from the fleet of the city of Loja in the period 2014 - 2013. Monitoring, considering that the wind speed does not matter what about 10 m/s and there is no precipitation was performed on primary and secondary streets and neighborhood Zamora Huayco center of the city of Loja, Monday to Sunday industry peaking of 7h00 to 9h00, 11h00 to 13h00 and 17h00 to 19h00; and, with a duration of 10 minutes for each point and two repetitions. Parallel to the monitoring of noise light and heavy vehicles and motorcycles will be counted. With the information obtained, noise maps, where the streets have higher sound pressure levels identified were developed; likewise the approach control measures mitigate noise pollution in the city of Loja. High levels of sound pressure occurred in most of the main and secondary streets, especially those circulating streets, more than light vehicles, heavy vehicles. These levels go over 65 dB, the permissible limits according Ecuadorian law, which determines that vehicular noise pollution. And in the neighborhood Huayco Zamora, sound pressure levels, most are under the established norm, which has acceptable noise levels. On maps of vehicular noise is observed in the center sector prevailing red color, indicating which surpass the permissible limits; and in the neighborhood Zamora Huayco dominates the yellow to green, showing that the sound pressure levels are low. Awareness to the citizens of Loja, which help the understanding of the problems of noise, training of stakeholders, and the use of alternative transportation - Identified areas of higher noise, the information measure is proposed.